UNDERSTANDING THE EFFECTS OF LIQUIDITY, PROFITABILITY, AND SALES GROWTH ON CAPITAL STRUCTURE: THE MODERATING ROLE OF COMPANY SIZE - Ramadhan, Patriot Dwiguna; Indrabudiman, Amir (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to examine the influence of liquidity, profitability, and sales growth on capital structure with company size as a moderating variable. This research uses 54 energy sector companies listed on the Indonesia Stock Exchange, selected using a purposive sampling method from the period 2018 to 2022. This research uses Moderated Regression Analysis (MRA) with the statistical method used to test the hypothesis is Jamovi version 2.3.28. The results of this research found that Liquidity has a significant positive effect on Capital Structure, Profitability has a significant positive effect on Capital Structure, Sales Growth has no significant effect on Capital Structure, Company Size moderates the effect positive of Liquidity on Capital Structure, Company Size cannot moderate the effect of Profitability and Growth Sales on Capital Structure.